The Design and Development of plaster molds for Large Industrial Pottery for the Community and Household Business - Kaewdee, Chatchai (Academic Journal of Industrial Technology Innovation, 2023)
This research aims to study the process of making plaster molds and to investigate the mixture ratio to form the large terracotta products and to design the plaster molds to create the large terracotta products which is suitable for household industrial production. The results showed that: 1) the appropriate process for creating plaster molds to form the large-scale terracotta products of the community, terracotta manufactures, and local materials in Nakhon Si Thammarat was to create each product by hand and mixed with the fibers from coconut husks; 2) the height of the product was in the range between 120 centimeters. The production period should not exceed seven days from the template and mole were created and such template should produce at least 60 pieces per mold; 3 ) The ratio for making plaster molds was a mixture between plaster, cement, and grout at the ratio of 90: 5: 5; and 4) manufacturers, suppliers and academic staff who interested in terracotta products were satisfied with the plaster mold for the production of large-sized workpieces at the highest level ( = 4.57, SD = 0.45).